2000
DOI: 10.1021/jo991787i
|View full text |Cite
|
Sign up to set email alerts
|

An Enantioselective Route to Paeonilactone A via Palladium- and Copper-Catalyzed Reactions

Abstract: We herein report on a formal total synthesis of paeonilactone A involving palladium-, copper-, and enzyme-catalyzed reactions starting from 1,3-cyclohexadiene. The key step in the synthesis, a palladium(II)-catalyzed 1,4-oxylactonization of a conjugated diene, simultaneously introduces two of the oxygen substituents required for the target molecule. The synthesis also includes our recently developed copper(I)-catalyzed cross-coupling reaction between dienyltriflates with Grignard reagents, introducing one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…In a demonstration of the synthetic utility of this oxidation, a key intermediate (174) in the synthesis of paenilactone A by Bäckvall and co-workers was constructed in two steps without compromising the enantiopurity (Scheme 75). [152] In 2004, Yokoyama et al described a protecting-groupfree total synthesis of the ergot alkaloid clavicipitic acid (177). [153] A chemoselective palladium-catalyzed Heck reaction/cyclization between 4-bromotryptophan (175) and 2-methyl-3-buten-2-ol (176) is the cornerstone of this synthesis (Scheme 76).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In a demonstration of the synthetic utility of this oxidation, a key intermediate (174) in the synthesis of paenilactone A by Bäckvall and co-workers was constructed in two steps without compromising the enantiopurity (Scheme 75). [152] In 2004, Yokoyama et al described a protecting-groupfree total synthesis of the ergot alkaloid clavicipitic acid (177). [153] A chemoselective palladium-catalyzed Heck reaction/cyclization between 4-bromotryptophan (175) and 2-methyl-3-buten-2-ol (176) is the cornerstone of this synthesis (Scheme 76).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…We synthesized diene 4 in racemic form and as separate enantiomers from the corresponding 2,4-cyclohexadienylacetic acids [9] (Supporting Information). The reactions were monitored by 1 H NMR spectroscopy and evaluated by using our SimFit program.…”
mentioning
confidence: 99%
“…The 13 C NMR (DEPT) spectrum displayed ten carbons ascribed to two quaternary carbons, four methines, two methylenes and two methyls. Careful analyses of its 1D and 2D NMR data indicated that compound 1 was a stereoisomer of 5,6-dihydroxy-3,6-dimethylhexahydrobenzofuran-2-one [28] but a different stereochemistry at C-6, which was supported by X-ray diffraction ( Fig. 4).…”
Section: Resultsmentioning
confidence: 81%